Antibacterial Coatings and Biofilm (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
In modern society, the use of plastic packaging is increasing, with countless and undeniable consequences. Although this type of packaging plays a significant role in the global economy and offers numerous advantages, it also has some drawbacks, particularly concerning environmental pollution. The motivation for this special issue stems from our passion for the latest research on environmentally friendly, active/edible, and intelligent packaging coatings with antibacterial properties. We aim to explore the antibacterial effects of different types of coatings on various bacteria, including their applications in the fields of food packaging and medicine.